PEMETAAN KARAKTER EKOSISTEM DAN SEBARAN DAERAH PENANGKAPAN IKAN MADIDIHANG (Thunnus albacores) DI PERAIRAN UTARA PAPUA (Ecosystem Character Mapping and Fishing Ground Spatial Distribution of Yellowfin Tuna (Thunnus albacores) in Northern Papua) - . Sepri (Bogor Agricultural University, 2012)
ABSTRACTThe research was aimed to study the condition of the seasonal ecosystem characters (water temperature, salinity, flow and depth) and the seawater temperature data from MODIS satellite, TRITON Buoy temperature, salinity, currents and depth of the hook in northern waters of Papua which is associated with fish catches of yellowfin tuna (Thunus albacores). The research method was based on a survey with emphasis on water parameters, ecosystems character which have a great influence of the fishing ground. The ecosystem variables that effecting fishing ground of yellowfin i.e. temperature, salinity, current and depth. Results from this study showed that the value of north Papua sea surface temperatures were relatively high during January and February, with the highest temperature in January 30.33 oC and relatively low in April with a temperature of 29.9 oC. In January - March, the salinity of the waters of north Papua 34-35.4 for each month and in depth, the current ranged from 4.4 to 39.1 cm/sec. The depth for setting the hook to catch yellowfin in a large numbers was mostly in between 177 and 219 meters, where temperatures ranged between 19.7 and 23.6 oC. Yellowfin monthly production in June to August and December 2010 to February 2011 showed a positive relationship between yellowfin catches and depth of water temperature (r = 0.544), depth of the hook (r = 0.533), salinity (r = 0.403) and current (r = 0.537). The results of multiple regression analysis showed a strong relationship to each variable parameters of temperature, depth, salinity and current (r = 0.611) of the catch.Key words: ecosystems, hook depth, mapping, temperature, yellowfin tuna——-ABSTRAKPenelitian ini bertujuan untuk mengkaji kondisi musiman karakter ekosistem (suhu perairan, salinitas, arus dan kedalaman) hasil pengukuran satelit MODIS dan data TRITON buoy serta pola sebaran suhu perairan, salinitas, arus dan kedalaman mata pancing di perairan Utara Papua yang dikaitkan dengan hasil tangkapan ikan madidihang/yellowfin tuna (Thunus albacores). Metode penelitian adalah metode survei dengan penekanan pada nilai variabel parameter perairan/ karakter ekosistem yang sangat berpengaruh terhadap daerah penangkapan ikan (fishing ground) madidihang yaitu suhu, salinitas, arus dan kedalaman. Hasil evaluasi penilaian secara umum menunjukkan bahwa, nilai suhu permukaan laut di utara Papua relatif tinggi pada bulan Januari dan Februari, dengan nilai tertinggi 30,33 oC dan relatif rendah pada bulan April dengan nilai 29,9 oC. Pada bulan Januari hingga Maret, massa air dengan salinitas berkisar 34 â€“ 35,4â€° untuk setiap bulan, dan di kedalaman di perairan utara Papua, kecepatan arus 4,4 - 39,1 cm/dt. Kedalaman mata pancing yang di-setting pada kedalaman 177 - 219 meter, dimana suhu berkisar antara 19,7 - 23,6 oC. Produksi bulanan madidihang pada Juni-Agustus dan Desember 2010-Februari 2011 menunjukkan hubungan positif antara hasil tangkapan madidihang dengan suhu perairan (r = 0,544), kedalaman mata pancing (r = 0,533), salinitas (r = 0,403) dan arus (r = 0,537). Hasil analisis regresi berganda menunjukkan hubungan yang kuat untuk setiap variabel parameter suhu, kedalaman, salinitas dan arus(r = 0,611) terhadap hasil tangkapan.Kata kunci: ekosistem, kedalaman mata pancing, pemetaan, suhu, yellowfin tuna